The Significance of Gender Equality in Economic Growth - Uswatun Khasanah; Hadi Sasana (Publindo Akademika, 2022)
This article aims to conceptually describe the relationship between the importance of gender equality in economy. By using theoretical foundations in Production Function: Theory Development, the results showed that good economic activities must promote gender equality through various means, such as economic development, expanding job opportunities, increasing worker productivity, and urging a new job market. This growth can eliminate economic inefficiencies and increase women's and men's economic involvement. As income increases, the gender gap in health, learning, and nutrition tends to decrease.